Stability assessment and coordinated impedance shaping strategy for DC bidirectional cascaded system with LC input filter. (February 2020) - Huang, Xucheng; He, Zhixing; Chen, Zhiyong; Liu, Yali; Wu, Wenhua; Xu, Qianming; Zhou, Leming; Luo, An
Highlights: Based on the small-signal impedance-based method, this paper focuses on the stability analysis and improvement of the dc bidirectional cascaded system. The Thevenin equivalent circuit of the bus voltage-controlled converter (the boost converter) and the Norton equivalent circuit of the power-controlled converter (the VSC) are established for stability analysis. Meanwhile, the effects caused by dc LC filter circuit are also considered. Research shows that the power flow, the dc-link inductor, the dc capacitor at the terminal of the VSC and the dc voltage loop of the boost converter have significant influence on the dc cascaded system stability. To improve the stability of this system, a coordinated impedance shaping strategy is proposed to reshape the converters' impedance of the bidirectional cascaded system. In the proposed strategy, the proportional controller is adopted for dc voltage regulation. The proposed strategy reduces the output impedance of the boost converter and increases the phase of input impedance for the VSC. Hence, the overall system type is reduced by one with lesser CPL interference and smaller impedance interaction demonstrated. Abstract: In the ac/dc hybrid power system, bidirectional dc/ac converters, LC input filters, and energy storage bidirectional dc/dc converters form the dc bidirectional cascaded system. However, the system suffers instability issue in the different power flows, especially when one of the converters is constant power-controlled. Furthermore, the LC filter circuit will increase the output impedance of the cascaded system, which degrade the stability margin and might lead to the dc bus voltage oscillation. In order to analyze and solve such instability issue of the bidirectional cascaded system, this paper presents an impedance-based stability assessment; then, a coordinated impedance shaping strategy based on the voltage proportional controller is proposed. The proposed strategy can reduce the output impedance of the dc bus voltage-controlled converter and increase the phase of input impedance for the constant power load simultaneously, thus increasing the stability margin. Moreover, the proposed strategy eliminates the steady-state error of dc voltage by introducing power feedforward control. Finally, the efficiency of this proposed control strategy and theoretical analysis are validated by simulation and experimental results.